The Management of Corporate Financial Disclosure: Opportunism, Ritualism, Policies, and Processes - Gibbins, Michael; Richardson, Alan; Waterhouse, John (Journal of Accounting Research, 1990)
Michael Gibbins, Alan Richardson, John Waterhouse, The Management of Corporate Financial Disclosure: Opportunism, Ritualism, Policies, and Processes, Journal of Accounting Research, Vol. 28, No. 1 (Spring, 1990), pp. 121-143